Vocalizations of three species of Plectrohyla (Hylidae: Hylinae), with comments on natural history - Chaves-Acuña, Wagner; Zúniga, Javier; Boza-Oviedo, Eduardo (Zootaxa, 2025)
Vocalizations of many species in the genus Plectrohyla Brocchi, 1877 remain underexplored. This study provides a description of the vocalizations of P. catracha (Porras & Wilson, 1987) and P. insolita (McCranie et al., 1993) and the re-description of the call of P. ixil Stuart, 1942. The advertisement call of P. catracha is a short pulsed call with ascending amplitude modulation, duration of 41 ± 8 ms (20–80 ms), dominant frequency of 2,761 ± 151 Hz (2,411–3,100 Hz), and pulse rate of 101 ± 13 pulses/s (67–150 pulses/s). The territorial call consists of a repertoire of short trills emitted in brief series of 3–6 calls, each with a duration of 15 ± 6 ms (4–20 ms), dominant frequency of 2,725 ± 410 Hz (2,067–3,100 Hz), and pulse rate of 158 ± 55 pulses/s (100–250 pulses/s). The series of territorial calls last 650 ± 110 ms (480–840 ms). Plectrohyla catracha vocalizes from vegetation and water surfaces, with peak activity during the rainy season. The advertisement call of P. insolita is a short, “click” sound and consists of a single, pulsatile call with descending amplitude modulation, duration of 60 ± 10 ms (50–70 ms), and dominant frequency of 1,894 ± 172 Hz (1,722–2,067 Hz). Plectrohyla insolita is less frequently encountered, calling from elevated positions over streams while also displaying egg-attendance of multiple clutches. Plectrohyla ixil produces a long, single, pulsatile call with ascending amplitude modulation, duration of 244 ± 28 ms (220–280 ms), and dominant frequency of 1,274 ± 83 Hz (1,125–1,312 Hz). We assessed the variation within the known acoustics of the clade composed by Plectrohyla, Sarcohyla Duellman et al., 2016 and Exerodonta Brocchi, 1879, and discuss some patterns in call parameters among species of these genera and other Hylini.